Seja f (x) = - 3x2 + 7x + 6, o resultado de f (-1) + f (2) é:
A 0
B 1
C 2
D 3
E 4
Soluções para a tarefa
Respondido por
7
Explicação passo-a-passo:
• f(-1) = -3.(-1)² + 7.(-1) + 6
f(-1) = -3.1 - 7 + 6
f(-1) = -3 - 7 + 6
f(-1) = -4
• f(2) = -3.2² + 7.2 + 6
f(2) = -3.4 + 14 + 6
f(2) = -12 + 14 + 6
f(2) = 8
• f(-1) + f(2) = -4 + 8
f(-1) + f(2) = 4
Letra E
jvpacola:
o 3x2 (é 3x ao quadrado)
Perguntas interessantes
Matemática,
9 meses atrás
Geografia,
9 meses atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás